2017
DOI: 10.1590/2359-3997000000223
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of thyroid volume in oldest-old individuals

Abstract: Objective: The aim of this study was to describe the relationship between thyroid volume and age, gender, anthropometric characteristics, and echogenicity in oldest-old subjects in an iodine-sufficient area. Subjects and methods: The study included 81 independent elderly individuals aged ≥ 80 years (65 [80.2%] women). We determined these individuals' anthropometric characteristics, body mass index (BMI), and lean body mass, as well as thyroid volume and echogenicity by ultrasonography. Results: We observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
2
5
2
Order By: Relevance
“…The mean thyroid volume was found to be greater in males than females and also in the right lobe compared to the left lobe in both genders [3]. We also found that the thyroid right lobe was larger than the left in our study, but this was not statistically significant (P > 0.05).The volume of the thyroid is influenced by age, gender, body mass index (BMI), lean body mass, iodine intake, genetic, geographic region, and environmental factors [3,4].…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The mean thyroid volume was found to be greater in males than females and also in the right lobe compared to the left lobe in both genders [3]. We also found that the thyroid right lobe was larger than the left in our study, but this was not statistically significant (P > 0.05).The volume of the thyroid is influenced by age, gender, body mass index (BMI), lean body mass, iodine intake, genetic, geographic region, and environmental factors [3,4].…”
Section: Discussioncontrasting
confidence: 58%
“…The mean thyroid volume was 11.3 ± 0.5mL in another study [10]. In our study, we found that the mean thyroid volume in the control group was 11.95 ± 1.90mL.It is observed that thyroid volume in elderly individuals has decreased by 20.5% [4]. The mean thyroid volume was found to be greater in males than females and also in the right lobe compared to the left lobe in both genders [3].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The main causes are environmental factors, in particular regional iodine intake, as well as individual factors such as gender, age, genes, and consumption behavior. However, size and shape of the thyroid glands are subject to a wide variability and large multinodular goiters continue to appear relatively frequently in clinical practice [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%